Pencak Silat Sebagai Atraksi Wisata Budaya Desa Gardu - Mutiara Pratiwi; Noveriza Pusparani; Eki Priady Sinaga; Rizqullah, Muhamad; Widanti, Afrima (TOBA: Journal of Tourism, Hospitality, and Destination, 2024)
Pencak silat is a cultural heritage that has been passed down from generation to generation in Gardu Village, North Bengkulu, Bengkulu Province. This martial art is not only a form of self-protection from threats or attacks in the surrounding environment, but also a local wisdom that is still maintained by the village community. This research aims to explore the practice of pencak silat in Gardu Village as well as its potential as a cultural tourism attraction. A descriptive method with a qualitative approach was used in this study to obtain comprehensive data and information. The results of observations and interviews show that the martial art of pencak silat in Gardu Village has strong historical and cultural values, and can be developed as an attractive tourist attraction for tourists. Pencak silat in Gardu Village is performed only by men and is still preserved to this day. This practice is passed down from generation to generation. This research provides valuable insights into the potential of pencak silat as a cultural asset that can be utilized for tourism development in Gardu Village. The findings can serve as a basis for efforts to preserve and promote local cultural heritage, as well as encourage community economic improvement through the culture-based tourism industry.